2022
DOI: 10.1002/ece3.9484
|View full text |Cite
|
Sign up to set email alerts
|

The ecological diversification and evolution of Teleosauroidea (Crocodylomorpha, Thalattosuchia), with insights into their mandibular biomechanics

Abstract: Throughout the Jurassic, a plethora of marine reptiles dominated ocean waters, including ichthyosaurs, plesiosaurs and thalattosuchian crocodylomorphs. These Jurassic ecosystems were characterized by high niche partitioning and spatial variation in dietary ecology. However, while the ecological diversity of many marine reptile lineages is well known, the overall ecological diversification of Teleosauroidea (one of the two major groups within thalattosuchian crocodylomorphs) has never been explored. Teleosauroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 70 publications
3
28
0
Order By: Relevance
“…S13 ). This pattern is consistent with other studies of jaw shape variation in vertebrates, in which MA appears consistently as one of the most important functional variables 30 , 56 , 57 , 59 . This reflects a trade-off between jaws with high bite force but slow closing versus jaws with low bite force but rapid closing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S13 ). This pattern is consistent with other studies of jaw shape variation in vertebrates, in which MA appears consistently as one of the most important functional variables 30 , 56 , 57 , 59 . This reflects a trade-off between jaws with high bite force but slow closing versus jaws with low bite force but rapid closing.…”
Section: Discussionsupporting
confidence: 92%
“…Mandible shape variation in sharks can be explained in terms of functional interpretations of the major shape differences. This helps validate assumptions that studies of shape variation in jaw structure can provide reasonable proxies for primary feeding ecology, as is commonly done in palaeobiological and macroecological studies 30 , 56 59 . The jaw-closing mechanical advantage (in-lever length/out-lever length) (hereafter “MA”) correlates strongly with PC1 scores ( R = 0.89, p < 0.001; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 55%
“…-Proexochokefalos heberti, the only large-bodied teleosauroid in the Pierce II Guild, clusters together with Machimosaurini of the Crunch Guild (see §4). This result was extensively discussed by Foffa et al [5] and in detail by Johnson et al [27], who showed that tooth specialization in Machimsaurini lagged behind mandibular adaptations linked to consuming large-bodied prey items. Similarly, we notice that geosaurines of the GDP-clade evolved their morphofunctional complex in advance of the dental adaptations that place them in the Cut guild.…”
Section: Discussionmentioning
confidence: 65%
“…In other words, it may be possible to derive ecologically informative patterns from analysing the size, shape and mechanical performance of marine reptile lower jaws through time. The macroevolutionary trajectories of plesiosaurs, ichthyosaurs and thalattosuchians have all been individually investigated [18,19,[22][23][24][25][26][27][28][29], but rarely are there comparisons across sympatric clades and within the same assemblage. This unexplored gap prevents us from understanding whether different groups converged upon analogous solutions under similar ecological/selection pressures and from investigating broad ecological phenomena (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2019a), to semiaquatic and semiterrestrial (Johnson et al . 2022) respectively. Although relatively more elongated, the humerus of Platysuchus multiscrobiculatus resembles that of extant crocodylians, namely in the shape and orientation of the proximal head, distal condyles, and position of the deltopectoral crest.…”
Section: Discussionmentioning
confidence: 98%